Randomized clinical study of wear of enamel antagonists against polished monolithic zirconia crowns. (January 2018) - Esquivel-Upshaw, J.F.; Kim, M.J.; Hsu, S.M.; Abdulhameed, N.; Jenkins, R.; Neal, D.; Ren, F.; Clark, A.E.
Abstract: Objectives: To test the hypothesis that there is no difference in the in vivo maximum wear of enamel opposing monolithic zirconia crowns, enamel opposing porcelain fused to metal crowns and enamel opposing enamel. Methods: Thirty patients needing single crowns were randomized to receive either a monolithic zirconia or metal-ceramic crown. Two non-restored opposing teeth in the same quadrants were identified to serve as enamel controls. After cementation, quadrants were scanned for baseline data. Polyvinylsiloxane impressions were obtained and poured in white stone. Patients were recalled at six-months and one-year for re-impression. Stone models were scanned using a tabletop laserscanner to determine maximum wear. Statistical analysis was performed using Mann-Whitney U to determine any significant differences between the wear of enamel against zirconia and metal-ceramic crowns. Results: Sixteen zirconia and 14 metal-ceramic crowns were delivered. There were no statistical differences in mean wear of crown types (p = 0.165); enamel antagonists (p = 0.235) and enamel controls (p = 0.843) after one year. Conclusion: Monolithic zirconia exhibited comparable wear of enamel compared with metal-ceramic crowns and control enamel after one year. Significance: This study is clinically significant because the use of polished monolithic zirconia demonstrated comparable wear of opposing enamel to metal-ceramic and enamel antagonists.